Mesler entrainment in alcohols - Sundberg-Anderson, R. K.; Saylor, J. R. (Experiments in fluids, 2014)
Mesler entrainment has been studied extensively in water and, more recently, in silicone oils. Studies of Mesler entrainment in liquids other than these are rare. The extant experimental results in water show significant irreproducibility both in the qualitative characteristics of Mesler entrainment and in the existence or nonexistence of Mesler entrainment when, for example, drops of the same diameter are released from the same height. In contrast, in silicone oils, Mesler entrainment is highly reproducible, essentially occurring either all of the time, or none of the time for a given set of conditions. A goal of the present work was to determine which of these two behaviors is the “standard” behavior—that is, to determine whether Mesler entrainment is typically repeatable or not. The experimental studies presented herein were conducted in three liquids that have not been the subject of detailed investigation to date: ethyl alcohol, isopropyl alcohol, and methyl alcohol. All of these alcohol results showed behavior very similar to that observed in silicone oils, suggesting that Mesler entrainment is typically repeatable and that water is an atypical fluid, causing irreproducible results. Additionally, we present data obtained in silicone oils and combine that with the alcohol data in an attempt to develop a combination of dimensionless groups that predicts the boundaries within which Mesler entrainment occurs for liquids other than water.